1996
DOI: 10.1136/thx.51.10.1048
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the acute effects on gas exchange of nasal ventilation and doxapram in exacerbations of chronic obstructive pulmonary disease.

Abstract: Background -Nasal intermittent positive pressure ventilation (NIPPV) is useful in exacerbations of chronic obstructive pulmonary disease (COPD) complicated by ventilatory failure. The effects of NIPPV were compared with those of the respiratory stimulant doxapram on gas exchange in patients with COPD and acute ventilatory failure. Methods -Patients admitted with acute exacerbations of COPD and type 2 respiratory failure (Pao2 <8 kPa and Paco2 >6.7 kPa) who did not improve with conventional treatment were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
6

Year Published

2000
2000
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(46 citation statements)
references
References 5 publications
0
40
0
6
Order By: Relevance
“…The infusion may be continued for several days with gradual reduction of the infusion rate over time. However its use, at least in the U.K., has declined probably due to the greater efficacy of other techniques such as nasal intermittent positive pressure ventilation as a temporizing measure in respiratory failure (2).…”
Section: Use As a Stimulant In Respiratory Failurementioning
confidence: 99%
“…The infusion may be continued for several days with gradual reduction of the infusion rate over time. However its use, at least in the U.K., has declined probably due to the greater efficacy of other techniques such as nasal intermittent positive pressure ventilation as a temporizing measure in respiratory failure (2).…”
Section: Use As a Stimulant In Respiratory Failurementioning
confidence: 99%
“…This drug is a potent stimulus to breathing in healthy individuals [33] but appears inferior to noninvasive positive pressure ventilation in COPD patients [34].…”
Section: Maintaining Gas Exchangementioning
confidence: 99%
“…Respiratory failure can be managed by giving parental respiratory stimulants with doxapram hydrochloride being the favourite drug. Reports over 30 years ago suggest that this might improve blood gas tensions, but more recent studies have found it inferior to noninvasive positive pressure ventilation in the management of significant hypercapnic exacerbations of COPD [41].…”
Section: Other Medicationsmentioning
confidence: 99%